EDUKASI MELALUI MEDIA VISUAL SEBAGAI BENTUK UPAYA PREVENTIF KONDISI STUNTING PADA ANAK-ANAK DI DESA SUNGAI LIRIK - Iin Ariyanti; Dimas Permana Putra; Mahrita Ilham, Naswa Adelia Puteri, Satrio Utomo, Sisca Ramdania Wati, Rizky Maulana, Dini Elya Nita (UMBanjarmasin, 2024)
The problem of malnutrition in a child's golden period can result in stunting which becomes a problem in the child's growth and development phase. In 2023, Barito Kuala Regency will occupy first place with the highest stunting rate of the 13 districts/cities in South Kalimantan province. One of the villages that is still above the stunting threshold is Sungai Lirik Village, Bakumpai District, Barito Kuala. Reducing stunting rates can begin by paying attention to childhood, which is a crucial and responsive period for every child to the surrounding environment. Not only food with balanced nutrition, but also other supporting factors that can influence children's growth and development. An experience that can create self-confidence and a positive attitude by involving fine motor skills through children's freedom to be creative so that development grows optimally. Activities that can support children's physical motoric involvement are through drawing media and puzzle media. The target of this activity is children in Sungai Lirik village aged 4 to 12 years with a total of 15 children participating. Activities were carried out using puzzle image media and booklet media through a community service program in Sungai Lirik village. The educational approach while playing can make it easier and more fun for children so that it will make it easier to process the information they absorb due to the happy feelings they feel. Apart from that, the use of visual media for children so that they understand and understand more about healthy food is a form of prevention effort against stunting which is often experienced by children who are experiencing the process of growth and development in the optimal phase in the future.